Mobile health use predicts self-efficacy and self-management in adolescents with sickle cell disease. Issue 10 (5th May 2021) - Hood, Anna M; Nwankwo, Cara; Walton, Ashley; McTate, Emily; Joffe, Naomi; Quinn, Charles T; Britto, Maria T; Peugh, James; Mara, Constance A; Crosby, Lori E
Abstract : Adolescents and young adults (AYA) with sickle cell disease (SCD) experience health challenges during the move from pediatric to adult care. Self-management (i.e., prioritizing and completing goals) and self-efficacy (i.e., confidence) are needed to manage a chronic disease effectively, but AYA with SCD often lack the skills. Mobile health (mHealth) technology (e.g., smartphones and tablets) present a way for AYA to monitor and track symptoms, change behaviors, and complete goals. We included a mHealth app into a group intervention (SCThrive) to see if using components of the app more frequently increased self-management and self-efficacy for AYA with SCD aged 13–21 years. We found that logging on to the app more often was related to better mood symptoms and lower pain ratings. AYA who logged onto the app more often reported more self-management skills and self-efficacy. Our findings indicate clinical benefits for those AYA with SCD who engaged with the mobile app. Abstract: Sickle cell disease (SCD) is associated with significant health challenges that often worsen during adolescence. Living with SCD requires a substantial amount of self-management and mobile health (mHealth) holds considerable promise for assessing and changing behaviors to improve health outcomes. We integrated a mobile app as an adjunct to a group intervention (SCThrive) and hypothesized that more engagement with the mHealth app would increase self-management and self-efficacy for adolescents and young adults (AYA) with SCD. Twenty-six AYA ages 13–21 years (54% female; 46% HbSS genotype; all African-American/Black) received six weekly group sessions (three in-person, three online). Participants were provided with the mobile app (iManage for SCD) to record progress on their self-management goals and log pain and mood symptoms. The Transition Readiness Assessment Questionnaire (TRAQ-5) assessed self-management skills and the Patient Activation Measure (PAM-13) assessed self-efficacy at baseline and post-treatment. Logging on to the app more frequently was associated higher mood ratings ( r = .54, CI[.18, .77], p = .006) and lower pain ratings ( r = −.48, CI[−.77, −.02], p = .04). Regression analyses demonstrated that after controlling for scores at baseline, the number of logins to the app predicted self-management skills ( p = .05, η 2 = .17) and possibly self-efficacy ( p = .08, η 2 = .13). Our study findings indicate that it can be challenging to maintain engagement in mHealth for AYA with SCD, but for those who do engage, there are significant benefits related to self-management, self-efficacy, and managing pain and mood.